Folded planar resonator-based sonic crystal scatterer: Part II. Tuning the local resonance. Issue 1 (April 2021) - Yahya, Iwan; Suparmi,; Cari,; Ubaidillah,
Abstract: This paper emphasized the tuning local resonance approach for proposing folded planar resonator-based sonic crystal scatterers. The folded inward design gives similar performance to the conventional single degree of freedom split tube resonator (STR). The sound absorption performance shifted to a lower frequency band according to the enlarging total volume of the resulting structure's volume without any significant effect from its inner wall thickness. Contrary to the folded outward direction design, which is resulting in multi-degree of freedom response. As the planar resonator folded in an outward direction, the resonator depth became a thin slit connecting the two separated cavities. The test model is made of stiff paper, as mentioned in part one. The entire laboratory test also conducted with a similar procedure refers to ASTM E-1050-98.